The Effect of Different Particle Sizes of Sweet Potato Flour on the Characteristics of Cookies - Jamaludin, Nursyafikah Aishah; Zainal Abidin, Munira; Zulhilmi Cheng, Mohamad Zulhafiz Shafiq (Enhanced Knowledge in Sciences and Technology, 2025)
Sweet potato (Ipomoea batatas) is a nutrient-packed crop abundant in protein, vitamins, minerals, and bioactive phytochemicals like polyphenols, dietary fiber, ascorbic acid, and beta-carotene. Cookies are widely consumed bakery products valued for their crispiness, chewiness, convenience, and ability to incorporate functional ingredients. This study aimed to evaluate the effect of incorporating sweet potato flour (SPF) of varying particle sizes (30, 60, and 120 mesh) into cookie formulations and assess their sensory acceptance. Four formulations were developed: a control (100% wheat flour) and three with SPF incorporated into wheat flour at different particle sizes. Results showed that the control cookies had the highest spread ratio (9.26) and lowest (3032g) hardness, while SPF30 exhibited the highest force (4671g) during the compression test, indicating a firmer texture. Among all formulations, cookies made with SPF120 received the highest overall acceptance scores, making it the most favourable formulation for enhancing cookie quality and nutritional value.